Peranan International Safety Management (ISM) Code sebagai Penunjang Keselamatan Pelayaran di atas Kapal pada Perusahaan Pelayaran di Surabaya - Mudiyanto (Universitas Hang Tuah, 2018)
a support for shipping safety on a Surabaya shipping company ship. The sample of this studyis the ship crews and shipping company employees of 50 respondents. With the help of the SPSSprogram used to analyze data. The results of data processing obtained multiple R values of 0.765 Themultiple correlation coefficient shows that between the variable Document of Compliance and SafetyManagement Certificate has a strong relationship to the variables of shipping safety, the coefficient ofdetermination is indicated by the R value of 0.765 means the variables X1 and X2 have a strongrelationship level towards the dependent variable Y. The value of R Square, which is equal to 0.5855,means that the effective contribution given by the variables X1 and X2 to the dependent variable Y is58.5%